Identifikácia rentgenových a gama zdrojov v optickej oblasti - Urban, Ondrej; Hroch, Filip; Masarykova univerzita. Přírodovědecká fakulta. Fyzikální sekce (2009)
Práca sa zaoberá testovaním metód na hľadanie kandidátov optických náprotivkov rentgenových a gama zdrojov objavených družicou INTEGRAL a publikovaných v~treťom IBIS/ISGRI katalógu.
In the presented work we test methods of determining candidates for optical counterparts to the X-ray and gamma-ray sources discovered by the INTEGRAL satellite and published from the biggest part in the third IBIS/ISGRI catalogue.
Vedoucí práce: Filip Hroch.
Bakalářská práce (Bc.)--Masarykova univerzita, Přírodovědecká fakulta, 2009.
Keywords: fotometrie; gama záření; rentgenové záření; gamma rays; photometry; X-rays; bakalářské práce